2000
DOI: 10.1190/1.1444863
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of fracture parameters from reflection seismic data—Part I: HTI model due to a single fracture set

Abstract: The simplest effective model of a formation containing a single fracture system is transversely isotropic with a horizontal symmetry axis (HTI). Reflection seismic signatures in HTI media, such as NMO velocity and amplitude variation with offset (AVO) gradient, can be conveniently described by the Thomsen‐type anisotropic parameters [Formula: see text] [Formula: see text] and [Formula: see text] Here, we use the linear slip theory of Schoenberg and co‐workers and the models developed by Hudson and Thomsen for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
211
0
13

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 509 publications
(230 citation statements)
references
References 33 publications
6
211
0
13
Order By: Relevance
“…Authors [12][13][14] use third-order elasticity theory to characterize 3D stress dependence elasticity and anisotropy. Authors [15][16][17] introduce nonlinear models consistent with empirically derived phenomenological equations [18]. Our interest in the discrete and analytic models described earlier (and in more detail below) is based on seeking formulations described using few and intuitive effective microstructural model parameters that can be calibrated with available data (e.g., ultrasonic core data).…”
Section: Rock Physics Modelmentioning
confidence: 99%
“…Authors [12][13][14] use third-order elasticity theory to characterize 3D stress dependence elasticity and anisotropy. Authors [15][16][17] introduce nonlinear models consistent with empirically derived phenomenological equations [18]. Our interest in the discrete and analytic models described earlier (and in more detail below) is based on seeking formulations described using few and intuitive effective microstructural model parameters that can be calibrated with available data (e.g., ultrasonic core data).…”
Section: Rock Physics Modelmentioning
confidence: 99%
“…Chichinina et al (2015) analyse the limitations of Schoenberg & Sayers (1995) LS model and find that their model is not generally adequate for real rocks. Chichinina et al (2015) note that the LS model is only valid for two conditions: (1) when Z N = 0 (i.e., case of fluid-filled fractures) or (2) when the scalar crack Z N /Z T = 1 is assumed (i.e., Bakulin et al, 2000). Hildyard (2001) observed that the LS model was only accurate for high-stiffness fractures and became increasingly inaccurate as the stiffness decreased, which is consistent with the first condition Z N = 0.…”
Section: Discussionmentioning
confidence: 99%
“…This model uses physically intuitive relations between stress and discontinuity in displacement across the fracture plane, and is formulated in terms of excess compliances (or weaknesses) of the material caused by the presence of fractures. It requires no assumptions about the microstructure or microgeometry of the fractures (Bakulin et al, 2000).…”
Section: Anisotropic Rock Property Prediction Workflowmentioning
confidence: 99%